2001
DOI: 10.1021/ja010066+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis ofent-Alantrypinone

Abstract: This paper presents a synthesis of ent-alantrypinone (ent-6), the enantiomer of a natural product produced by the fungus Penicillium thymicola. The synthesis revolves around the Li[Me(3)AlSPh]-promoted isomerization of iminobenzoxazine 33 to quinazolinone 34, an N-acyliminium ion cyclization that converts enamide 9 to bridged indole 35, and rearrangement of 35 to oxindole ent-6. Ancillary chemistry that involves thermal fragmentation of an iminobenzoxazine to a nitrile ylide and Me(2)AlSPh-mediated cyclization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…We finally elucidated the structure of compound 1 as (-)-(1R,4R)-1,4-(2,3)-indolmethane-1-methyl-2,4-dihydro-1H-pyrazino-[2,1-b]-quinazoline-3,6-dione, a known quinazoline alkaloid synthesized as a precursor for (-)-alantrypinone (Hart & Magomedov, 1999). To the best of our knowledge, this is the first time that compound 1 has been found in plant endophytes, although fungi belonging to the genera Penicillium serve as a rich source of alkaloids clearly derived from amino acids (Hart & Magomedov, 2001). These quinazoline alkaloids have been reported to show moderate cytotoxicities in vitro (Takahashi et al, 1995).…”
mentioning
confidence: 93%
“…We finally elucidated the structure of compound 1 as (-)-(1R,4R)-1,4-(2,3)-indolmethane-1-methyl-2,4-dihydro-1H-pyrazino-[2,1-b]-quinazoline-3,6-dione, a known quinazoline alkaloid synthesized as a precursor for (-)-alantrypinone (Hart & Magomedov, 1999). To the best of our knowledge, this is the first time that compound 1 has been found in plant endophytes, although fungi belonging to the genera Penicillium serve as a rich source of alkaloids clearly derived from amino acids (Hart & Magomedov, 2001). These quinazoline alkaloids have been reported to show moderate cytotoxicities in vitro (Takahashi et al, 1995).…”
mentioning
confidence: 93%
“…Hart and coworkers have expressed interest in the biosynthesis of the fumiquinazoline family of alkaloid natural products, and reported a biomimetic synthesis of ent-alantrypinone as the initial effort at a synthetic program to access more complex, related substances [38]. l-Tryptophan methyl ester was coupled to isatoic anhydride to afford amide 184 in good yield (Scheme 4. work, Movassaghi and coworkers showed that cleavage of the N-Boc carbamate was accompanied by cyclization to dioxopiperazine 204 (Scheme 4.35) [39].…”
Section: Non-prenylated Indole Alkaloidsmentioning
confidence: 99%
“…22,23 This research was actually a diversion of a synthetic program directed at spiroquinazoline 1, whose synthesis from Ltryptophan was being pursued when the structure of 7 was reported. 6 The late stages of the synthetic plan were inspired by the biosynthetic speculation described in Section 3 of this review (Scheme 1).…”
Section: Total Synthesis Of Alantrypinone (7) and Ent-alantrypinone (mentioning
confidence: 99%